Is there a relationship between horizontal jump and sprint performance in professional amputee football players? (Annals of Medical Research, 2021)
Aim: Although amputee football is not a Paralympic branch, it is growing in popularity. It has some differences compared to regular football, and it also requires high levels of flexibility, endurance, strength, power, speed and, agility as normal football. However, the relationship between sprint and jumping performance in amputee football players has not been fully revealed. The aim of this study is to determine the relationship between one leg hop and sprint performance in professional amputee football players.Material and Methods: Twelve Amputee Super League football team players participated in the study. One leg hop performance of the players was evaluated with the one leg hop test, and the sprint performance was evaluated with 10m, 20m and 30m sprint tests. The relationship between the performances was examined with Spearman’s Correlation.Results: The study revealed that there is a significant relationship between the one leg hop and 20m (p=0.001), 30m sprint performances (p=0.001), but no relationship with the 10 m sprint test (p=0.117). Conclusion: The results of the study showed that 20m, 30m sprint and horizontal jump performances of the amputee football players were correlated and the other not. Given that amputee football is a sport with different dynamics, new studies are needed to shed light on the power mechanisms necessary for performance.